Evaluation of phloxine B as a photoinsecticide on immature stages of the horn fly, Haematobia irritans (L.) (Diptera: Muscidae) - Filiberti, Adrian (2009)
The use of photoactive substances for controlling adult or immature stages of insect pests is an attractive alternative to chemical insecticides. Phloxine B is an environmentally friendly xanthene derivative that is safe for mammals but toxic for dipterans. In this study we tested the effect of phloxine B as a phototoxic larvicide against immature stages of the blood-sucking horn fly, Haematobia irritans (L.). The mortality rate of phloxine B was very low in the dark during the larval stage (100 h) unless a 0.5-mM dye concentration was used. However, a high mortality rate was attained when larvae III were transferred to containers exposed to 5000 lux during the last 2 h before pupariation. This was concentration-dependent up to 0.1-mM phloxine B. After a 2-h larval exposure to light the phloxine B 50% lethal concentration was 0.043 mM. These results indicate that H. irritans larvae are very sensitive to this dye, which in turn seems a promising component for larvicide formulations to control horn flies